2013
DOI: 10.1093/carcin/bgt346
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of KAI1/CD82 in human melanoma and its role in cell migration and invasion through the regulation of ING4

Abstract: KAI1/CD82 is a member of the transmembrane 4 superfamily, which was first identified as a metastasis suppressor for prostate cancer. The expression of KAI1 was found to be reduced in many types of cancers, including prostate, breast, ovarian, cervical and endometrial cancer. However, the role of KAI1 in melanoma pathogenesis is not known. In this study, we investigated the expression level of KAI1 in a large set of melanocytic lesions at different stages. We found that the expression of KAI1 is significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 32 publications
6
31
0
Order By: Relevance
“…Secondly, the other function of KAI1/CD82 protein could be considered in gliomas like regulation by microRNA. An experimental study has shown that KAI1/CD82 is able to inhibit the signaling PI3K/AKT pathway in breast, bladder, and melanoma cancer cell lines [23,24]. Taking into account that the PI3K/ AKT pathway is often activated by PDGFR receptors during glioma progression, we suggest that the suppression of the PI3K/AKT pathway by KAI1/CD82 protein might limit the proliferation and spread of glioma cells [19,23].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Secondly, the other function of KAI1/CD82 protein could be considered in gliomas like regulation by microRNA. An experimental study has shown that KAI1/CD82 is able to inhibit the signaling PI3K/AKT pathway in breast, bladder, and melanoma cancer cell lines [23,24]. Taking into account that the PI3K/ AKT pathway is often activated by PDGFR receptors during glioma progression, we suggest that the suppression of the PI3K/AKT pathway by KAI1/CD82 protein might limit the proliferation and spread of glioma cells [19,23].…”
Section: Discussionmentioning
confidence: 84%
“…Recently, data revealed that upregulation of micro-RNA-210 induced cell proliferation and migration of glioblastoma cells [32]. We postulate that KAI1/CD82 protein expression in gliomas might play a similar role to that in tumors with metastasis to other organs [7,23]. Firstly, KAI1/CD82 as a metastasis suppressor protein might inhibit the migratory ability of glioma cells, so we suggest that a high expression of KAI1/CD82 in low grade gliomas might reduce the risk of secondary glioblastoma development.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[14] The studies suggest that KAI1 may be used as a promising prognostic marker and a possible therapeutic target for human melanoma. [15] Decreased KAI1 expression has been observed recently in various human cancers, including pancreatic, lung, hepatic, colorectal, breast, ovarian, esophageal, and cervical cancers. Frequent down-regulation of the KAI1 protein was also observed in endometrial cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%